2005
DOI: 10.1007/s11064-005-2684-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Aspartate Release by Ascorbic Acid and Endobain E, an Endogenous Na+, K+-ATPase Inhibitor

Abstract: The isolation of a soluble brain fraction which behaves as an endogenous ouabain-like substance, termed endobain E, has been described. Endobain E contains two Na+, K+ -ATPase inhibitors, one of them identical to ascorbic acid. Neurotransmitter release in the presence of endobain E and ascorbic acid was studied in non-depolarizing (0 mM KCl) and depolarizing (40 mM KCl) conditions. Synaptosomes were isolated from cerebral cortex of male Wistar rats by differential centrifugation and Percoll gradient. Synaptoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…-ATPase inhibitor, termed endobain E, which shares several biological properties with ouabain. They include the blockade of high affinity [ 3 H]ouabain binding [42], norepinephrine release enhancement [43] and uptake decrease [44] from rat hypothalamus slices, excitatory amino acid release enhancement from synaptosomes [19], as well as phosphoinositide turnover increase [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-ATPase inhibitor, termed endobain E, which shares several biological properties with ouabain. They include the blockade of high affinity [ 3 H]ouabain binding [42], norepinephrine release enhancement [43] and uptake decrease [44] from rat hypothalamus slices, excitatory amino acid release enhancement from synaptosomes [19], as well as phosphoinositide turnover increase [45].…”
Section: Discussionmentioning
confidence: 99%
“…Ouabain evokes the release of neurotransmitters in several experimental models, including that of excitatory amino acids from cerebral cortex synaptosomes [18,19], and from cerebellar granule cells in culture [4]. Besides, ouabain is responsible for an increase in intracellular sodium concentration and depolarization of the plasma membrane, as well as for calcium entry to the cell through several calcium channels, including those related to NMDA receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Ouabain induces several effects in brain neurotransmission: it increases the release of aspartate and other amino acids [14,15]; decreases norepinephrine uptake [16] and increases its release [17]; blocks the uptake of dopamine [18] and increases its release [14]; decreases the binding of muscarinic antagonist [19] and it induces the release of acetylcholine [14,20]. Some of these effects of ouabain are also induced by the endogenous ouabain-like substance [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these effects of ouabain are also induced by the endogenous ouabain-like substance [15][16][17]. Recently, other effects of the interaction of ouabain with the sodium-potassium/ATPase were demonstrated and involve the induction of intracellular signaling molecules as a result of the binding of ouabain to the sodium-potassium/ATPase and promoting the interaction between sodium-potassium/ATPase and other proteins in the cell membrane, such as tyrosine kinase Src [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…18 Vitamin C modulates brain neurotransmitter system mainly glutaminergic,dopaminergic, cholinergic and serotonergic that are linked in memory, learning and cognitive function, moreover ,vitamin C regarded as important cofactor in the synthesis and releasing of noradrenaline and cerebral acetylcholine 19 ,this may explained the cognitive enhancing effects of lipoic acid that augments endogenous cerebral ascorbate level in aged and healthy subjects also , neurobehavioral effect of different herbs was explained depending on their antioxidant properties . 20 Animal model study showed that mice deficient in gene encoding for vitamin C lactone oxidase developed a sever cognitive impairment due to oxidative stress that measured by F4-neuroprostans, also, vitamin C reverses and attenuate scopolamine induced cognitive impairment in rats due to stimulation of central acetylcholineastrase enzyme at median forebrain bundle or through activation of cholinergic neurons, and in spite of vitamin C does not cross blood brain barrier, 21,22 therefore ,oral and intraperitoneal administration of vitamin C will not elevates cerebral ascorbate level ,but lipoic acid elevate brain ascorbate concentration that be able for central arousal effects which improve attention and learning due to modulation of hippocampal and forebrain glutamate concentration. Moreover, lipoic acid may improve psychomotor performance through its modulator effects on glutamate receptor which per see improve a brain nitric oxide.…”
Section: Resultsmentioning
confidence: 99%